Cost-effectiveness of therapeutic infant formulas for cow's milk protein allergy management - Suratannon, Narissara; Prapansilp, Panote; Srinarongsook, Athitaya; Tanpowpong, Pornthep; Chatchatee, Pantipa; Pongpirul, Krit (Frontiers in Nutrition, 2023)
Cow's milk protein allergy (CMPA) is children's most common food allergy. Therapeutic infant formulas for CMPA lead to symptom-free and potentially benefit early tolerance induction and reducing the allergic march in non-breastfed babies. This study assessed the cost-effectiveness of CMPA management with different therapeutic infant formulas in Thailand, which may reflect situations in developing countries throughout Asia. An analytic decision model was developed to simulate the occurrence of eczema, urticaria, asthma, rhinoconjunctivitis, or being symptom-free in infants with CMPA over 36 months. Extensively hydrolyzed casein formula with added probiotic Lacticaseibacillus rhamnosus (previously Lactobacillus rhamnosus) strain GG (EHCF+LGG), extensively hydrolyzed whey formula (EHWF), soy protein-based formula (SPF) and amino acid formula (AAF) were compared from the healthcare payer perspective. Results from a prospective cohort study were used for comparative effectiveness measures, while local experts were interviewed to estimate the healthcare resource used in the management of CMPA. The costs of healthcare resources were obtained from standard, publicly available sources. The direct medical cost of CMPA management was lowest for EHCF+LGG (USD 1,720), followed by SPF (USD 2,090), EHWF (USD 2,791), and AAF (USD 7,881). Compared to other formulas, EHCF+LGG was expected to save USD 370 (SPF), USD 1,071 (EHWF), and USD 6,161 (AAF) in the total cost of CMPA management over 36 months. In conclusion, EHCF+LGG was the most cost-effective strategy for managing non-breastfed infants with CMPA. This strategy was associated with more children developing immune tolerance to cow's milk and being symptom-free, contributing to overall cost-saving potential.